Inventarisasi Anggrek Tanah Pada Kawasan Kebun Bonsai dan Sekitarnya di Desa Padang Bujur, Cagar Alam Dolok Sibual-buali, Provinsi Sumatera Utara - Humayra Nasution; Pindi Patana; Yunasfi Yunasfi (Peronema Forestry Science Journal, 2014)
Dolok Sibual-buali Nature Reserve (CADS) is a conservation area in North Sumatra, covers ± 5.000 hectare area, altitude 1.200 – 1.700 m asl. Terrestrial orchids are orchids that grow in the ground in soil and the nutrition is obtained from the soil. Inventory of terrestrial orchids performed to study the diversity and altitudinal distribution of terrestrial orchids species in CADS. Study was performed in April - July 2013. Locations are determined by purposive sampling study with noticed the environmental factors, the vegetation observation used line plot transect which divided into 4 locations with different altitude intervals of every 100 m (1.200 m asl – 1.600 m asl), measuring plot 20 m x 100 m, divided to 5 subplots measuring 20 m x 20 m, so the plot number is 20.  The result found 29 species of terrestrial orchids, divided of 17 genus with the individuals amount as much 816/0,8 hectare. Plocoglottis sp. 1 is the most widely distribution of species, found from 1.200 m asl to 1.500 m asl.Keywords: terrestrial orchids, Dolok Sibual-buali Nature Reserve, inventory, Kebun Bonsai.